Composite indicators of flexibilization across EU regions: a critical re-appraisal and interpretation - Stelios Gialis; Lila Leontidou; Michael Taylor (European Regional Science Association (ERSA), 2014)
The aim of the paper is to present a comparative analysis of the diffusion of ?flexible contractual arrangements' (FCA) across the European Union (EU). The homonymous FCA Composite Indicator (CI) is calculated for all 200 NUTS II-level regions of France, Germany, the UK, Denmark, Sweden, Belgium, Greece, Italy, Spain, Portugal, Bulgaria and Romania. The CI is calculated for 2005, 2008 and 2011 to present a clear picture of causal effects leading up to, and arising from, the 2008 financial crisis and ensuing recession. A total of eight (8) sub-indicators, grouped into three (3) distinct pillars, are synthesized into the common FCA CI. The novelty of the study lies on that is the first research attempt that accounts for a regional FCA CI by critically re-appraising existent methodology. The findings, and the cluster and outlier analysis performed on them, depict that the crisis had more intense consequences in certain regions than in others, and thus its effects upon regional labour markets were spatially uneven. As discussed in the paper, such an unevenness runs along, and cuts across, a variety of scales, namely the global, the EU and the intra-EU ones. All regions that are at the top of the FCA CI ranking, namely all Greek and more than half of the Spanish, Portuguese, Bulgarian and Romanian regions, are socio-spatial entities that lack advanced economic and social or welfare structures while at the same time facing important pressures from international and EU competitors. The paper stresses that the search for less rigidity and enhanced employability in labour markets, observed in the official policies of EU and national authorities since mid-1990s or so, reflects an agenda for re-regulating employment protection and security norms according to new accumulation priorities. Indeed, different flexibilizing mechanisms, related to increasing global competition and de-stabilized modes of social reproduction across the EU, and within its regions, are seen to have reinforced each other many years before the current crisis occurred. These trends seem to exacerbate in the post-2008 period leading poor forms of atypical work and high flexibilization to prevail, especially in the less privileged Southern and Eastern EU regions. Based on the FCA CI findings, the paper ends by arguing that CIs analysis may prove to be useful when not considered as a goal per se; rather, it should be seen as a first step towards in-depth and focused research, and the triggering of discussion on issues of social action and political intervention.
Keywords: J41; J21; 330